Hygiene Air Rumah Tangga Sebagai Faktor Resiko Kejadian Stunting pada Balita - Zakiah Zakiah; Aulina Adamy; Faisal Bin Abdurrahman; Radhiah Zakaria (FORIKES, 2022)
Stunting is not only caused by a lack of nutrients, it is suspected that it also occurs due to other factors. This study aims to determine the relationship between household water hygiene and the incidence of stunting in toddlers in Central Aceh District. This was an analytic observational study using a case-control design. The samples in the study were 54 toddlers (24-59 months), consisting of 27 cases and 27 controls. The data that had been collected was analyzed using a multiple logistic regression test to determine the most dominant factor influencing the incidence of stunting. The results of the bivariate analysis showed that there was no relationship between the water factor, namely the source of drinking water, access to drinking water and the incidence of stunting. However, unprotected drinking water sources havd a 1.4 times greater risk of having stunted children than protected drinking water sources. Difficult access to drinking water was also 1.4 times at risk of having stunted toddlers compared to easy access to drinking water. The results of the bivariate analysis on behavioral factors also show that there was no relationship between the factors of latrine ownership, proper sanitation, hand washing habits and the incidence of stunting. However, without a latrines, the risk was 1.3 times greater for having stunted children under five, besides that inadequate sanitation was also 1.1 times more likely to had stunted children under five. Mothers with poor hand washing habits was 1.5 times more likely to have stunted toddlers.Keywords: stunting; toddler; hygieneABSTRAK Stunting selain disebabkan karena kekurangan zat gizi, diduga juga terjadi akibat faktor lainnya. Penelitian ini bertujuan untuk mengetahui hubungan antara hygiene air rumah tangga dengan kejadian stunting pada balita di Kabupaten Aceh Tengah. Penelitian ini bersifat observasional analitik menggunakan rancangan case-control. Sampel dalam penelitian sebanyak 54 balita (24-59 bulan), terdiri atas 27 case dan 27 control. Data yang telah terkumpul dianalisis dengan uji regresi logistik ganda untuk mengetahui faktor yang paling dominan mempengaruhi kejadian stunting. Hasil analisis bivariat menunjukkan bahwa tidak ada hubungan antara faktor air yaitu sumber air minum, akses air minum dengan kejadian stunting. Namun sumber air minum tidak terlindungi berisiko 1,4 kali lebih besar memiliki balita stunting dibandingkan dengan sumber air minum terlindungi. Akses air minum sulit juga berisiko 1,4 kali memiliki balita stunting dibandingkan dengan akses air minum mudah. Hasil analisis bivariat pada faktor perilaku juga diketahui bahwa tidak ada hubungan antara faktor kepemilikan jamban, sanitasi layak, kebiasaan cuci tangan dengan kejadian stunting. Namun ketiadaan jamban berisiko 1,3 kali lebih besar memiliki balita stunting, selain itu sanitasi tidak layak juga berisiko 1,1 kali memiliki balita stunting. Ibu dengan kebiasaan cuci tangan kurang baik berisiko 1,5 kali lebih besar memiliki balita stunting.Kata kunci: stunting; balita; hygiene